Effect of Drying Conditions and Jojoba Oil Incorporation on the Selected Physical Properties of Hydrogel Whey Protein-Based Edible Films - Sabina Galus; Magdalena Karwacka; Agnieszka Ciurzyńska; Monika Janowicz (Gels, 2024)
Edible hydrogel coatings or films in comparison to conventional food packaging materials are characterized as thin layers obtained from biopolymers that can be applied or enveloped onto the surface of food products. The use of lipid-containing hydrogel packaging materials, primarily as edible protective coatings for food applications, is recognized for their excellent barrier capacity against water vapor during storage. With the high brittleness of waxes and the oxidation of different fats or oils, highly stable agents are desirable. Jojoba oil obtained from the jojoba shrub is an ester of long-chain fatty acids and monovalent, long-chain alcohols, which contains natural oxidants α, β, and δ tocopherols; therefore, it is resistant to oxidation and shows high thermal stability. The production of hydrogel films and coatings involves solvent evaporation, which may occur in ambient or controlled drying conditions. The study aimed to determine the effect of drying conditions (temperature from 20 to 70 °C and relative humidity from 30 to 70%) and jojoba oil addition at the concentrations of 0, 0.5, 1.0, 1.5, and 2.0% on the selected physical properties of hydrogel edible films based on whey protein isolate. Homogenization resulted in stable, film-forming emulsions with bimodal lipid droplet distribution and a particle size close to 3 and 45 µm. When higher drying temperatures were used, the drying time was much shorter (minimum 2 h for temperature of 70 °C and relative humidity of 30%) and a more compact structure, lower water content (12.00–13.68%), and better mechanical resistance (3.48–3.93 MPa) of hydrogel whey protein films were observed. The optimal conditions for drying hydrogel whey protein films are a temperature of 50 °C and an air humidity of 30% over 3 h. Increasing the content of jojoba oil caused noticeable color changes (total color difference increased from 2.00 to 2.43 at 20 °C and from 2.58 to 3.04 at 70 °C), improved mechanical elasticity (the highest at 60 °C from 48.4 to 101.1%), and reduced water vapor permeability (the highest at 70 °C from 9.00·10−10 to 6.35·10−10 g/m·s·Pa) of the analyzed films. The observations of scanning electron micrographs showed the heterogeneity of the film surface and irregular distribution of lipid droplets in the film matrix.